PERITONSILLITIS: CAUSES, SYMPTOMS, AND TREATMENT - Khondamir Jorayev; Sanjar Usmonov (Western European Studies, 2024)
The oropharynx and the larynx are considered to be the most affected areas of the digestive system and respiratory system. Teeth and other infectious diseases of the oral cavity, acute and diseases of the nose and nasal cavities cause the pharynx and palate to be affected, which makes it difficult to breathe through the nose. Diagnosis and treatment of acute or chronic inflammation of the palate in the early stages can prevent paratonsillitis and its dangerous complications. Enter. Peritonsillitis is one of the most severe in otorhinolaryngological practice. Literally translated, the diagnosis means "inflammation around the tonsils". acute purulent process here in direct penetration. The essence of the pathology, in fact, lies in the penetration of the pathogenic microorganism into the soft tissues of the peritonsillar area, where an acute purulent process begins. It should be noted that a complication of paratonsillitis is a paratonsillar abscess: a cavity filled with necrotic masses is formed due to the purulent process of the tonsil tissue.There are three forms of paratonsillitis that come to the otorhinolaryngologist doctor with different severity: swelling (5%), infiltrative (20%) and abscess (75%, that is, most of the patients are complicated by abscess).
Keywords: Peritonsillitis; Peritonsillar abscess; Tonsillitis